The Concept of Work-Life Balance and Practical Application for Customer Services of Bank - Lestari, Dirga; Tricahyadinata, Irsan; Rahmawati, Rahmawati; Darma, Dio Caisar; Maria, Siti; Heksarini, Ariesta (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
This paper aims to examine the work-life balance (WLB) standards applied by the Limited Company of Bank Central Asia (PT BCA) Samarinda branch and their impact on employee loyalty, job performance, and turnover intentions. Our targets for employees who work in customer services (CS). We collected the data through survey techniques, where the size of the informants was 340 samples. Multiple regression analyses indicate that the WLB policy has affected employee loyalty, turnover intentions, and job performance. Employee loyalty also plays an essential role in job performance and turnover intentions. Meanwhile, job performance has a significant effect on preventing turnover intentions. The fundamental difference to this finding lies in the escalation in the causality of the variables and is worth developing.